Design thinking jako element rozwoju innowacji społecznych - Hałub, Przemysław (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article refers to the concepts of social innovation and design thinking. The author emphasizes that technological innovation and social innovation are separate areas, however they may reveal many points of contact (touch-points) and interactions. The author points to the possibilities of using design thinking in the development and creation of social attitudes that influence the development of the economy. It indicates the number of interactions between technology and integrated development of society. The author focuses on the description of the phenomena associated with the development of knowledge-based economy in Poland and Polish situation in the area of new technologies — opportunities and barriers. Design thinking may appear as a tool that can be used through creating new and integrated values for society and technology development. Design thinking is defined as a method of creating new products and services based on deep understanding of the problems and needs of the users. The aim of the method is to create and introduce innovative solutions not only in the form of new products and technologies, but also services, strategies, processes, business models and even educational programs. The design thinking method is based on the work of interdisciplinary teams — looking at the problem from multiple perspectives, experimentation and frequent testing of hypotheses. It concentrates on prototyping culture and testing and combines analytical methods with an intuitive approach, based on empathy and creativity. It strongly relates to the idea of social innovation. The author emphasises that in some cases it is possible to define a gap between technological concepts and social needs, and design thinking could be one of the tools and methods that bring them together
Keywords: social innovation; design thinking; economy development; technology; creativity